Acupuncture for Patients with Lumbar Spinal Stenosis: A Randomised Pilot Trial. Issue 4 (August 2016) - Kim, Kun Hyung; Kim, Yu Ri; Baik, Seung Kug; Noh, Seung Hee; Kim, Dae Hun; Lee, Sang Weon; Yang, Gi Young
Objective: To assess the safety and feasibility of acupuncture for participants with symptomatic lumbar spinal stenosis (LSS) in a pilot study. Methods: 50 participants with a clinical and radiological diagnosis of LSS were randomised to receive acupuncture combined with usual care (acupuncture group), or usual care alone (control group). Participants in the acupuncture group were offered 12–16 sessions of manual acupuncture±electroacupuncture over 6 weeks and maintained their usual self-management. The control group was provided with physical therapy as required and maintained their usual self-management. The primary outcome was the change in back-specific functional status, as measured by the Oswestry disability index (ODI) at the 3-month follow-up. Secondary outcomes included symptoms and other relevant domains. Outcome assessors were not blinded. Results: 39 participants (78%) completed the trial with 524 treatment visits. There were no significant differences between the two groups in back-specific function (ODI: mean difference −2.5, 95% CI −8.9 to 3.8). Pain in the back and/or leg showed small improvements at 3 months, while there were no significant differences in other secondary outcomes. The total number of adverse events was 61 (12% of 524 treatment visits). All but one were minor and transient. The one severe adverse event was deemed to be unrelated to acupuncture. Conclusions: The study was feasible. Acupuncture combined with usual care did not confer significant functional improvements over usual care alone. Further randomised trials with adequate sample sizes and outcome assessor blinding are warranted to evaluate the role of acupuncture for LSS. Trial Registration Number: NCT01987622.